Horseradish peroxidase production from Spodoptera frugiperda larvae: A simple and inexpensive method - Targovnik, Alexandra Marisa (2010)
Horseradish peroxidase is used in many biotechnological fields including diagnostics, biocatalysts and biosensors. Horseradish peroxidase isozyme C (HRPC) was extracellularly expressed in Spodoptera frugiperda Sf9 cell culture and in intact larvae. At day 6 post-infection, the concentration of active HRPC in suspension cultures was 3.0 ± 0.1 μg per 1 × 106 cells or 3.0 ± 0.1 mg l-1 with a multiplicity of infection of 1 in the presence of 7.2 μM hemin. Similar yields were obtained in monolayer cultures. In larvae, the HRPC expression level was 137 ± 17 mg HRPC kg-1 larvae at day 6 post-infection with a single larvae thus producing approximately 41 μg HRPC. The whole larval extract was separated by ion exchange chromatography and HRPC was purified in a single step with a yield of 75% and a purification factor of 117. The molecular weight of recombinant HRPC was 44,016 Da, and its glycosylation pattern agreed with that expected for invertebrates. The Km and Vmax were 12.1 ± 1.7 mM and 2673 ± 113 U mg-1, respectively, similar to those of HRP purified from Armoracia rusticana roots. The method described in this study, based on overexpression of HRPC in S. frugiperda larvae, is a simple and inexpensive way to obtain high levels of active enzyme for research and other biotechnological applications. © 2010 Elsevier Ltd. All rights reserved.